On the Design and Development of a Zigbee-Based Multimodal Input-Output Monitoring-Actuating System - Abbas Orand; Y. Tomita; Sayaka Okamoto; Shigeru Sonoda (Institute of Advanced Engineering and Science, 2015)
The monitoring of a physically challenged patient’s activities is a crucial and difficult task for the medical professionals. The design and development of a multimodal- input and output wireless system with two sensors and three actuators that can be used for just monitoring or for both monitoring and stimulating are discussed in this research. Touch and tilt sensors at the input part of the system attached to Zigbee modules communicate in a wireless manner with voice, vibration and light actuators connected to Zigbee modules at the output part. The hardware and the software parts are designed and integrated in such a way that a new sensor at the input or a new actuator at the output can be included or excluded based on the needs of the patient. It is shown how to design and develop sensors. In an application programming interface communication mode, 3 XBee series 1 modules send and receive data in a wireless manner. The prototype of the system was tested with promising results in the case of the patients with inattention disorder. This system can be used for monitoring the activities of a patient and also for actuating certain stimulus in the patient side in case of necessity.